The Effect of Thyroxine (T4) Hormone Treated by Immersion toward the Growth and Survival of Nilem (Osteochilus hasselti) with Recirculation System - Wika Sepriani; Rusliadi Rusliadi; Niken Ayu Pamukas (Jurnal Akuakultur SEBATIN, 2024)
This study aims to determine the effect and optimal doses of thyroxine on the growth and survival of nilem. The test fish used came from Payakumbuh City, West Sumatra. The research was carried out at the Aquaculture Technology Laboratory, Faculty of Fisheries and Marine Affairs, Riau University, Pekanbaru, from April–May 2022. The method used in this study was a completely randomized design (CRD) experimental method. The research treatments were: P0 (without giving thyroxine hormone), P1 (0.7 mg/3L water), P2 (1.1 mg/3L water), P3 (1.5 mg/3 l water), and P4 (1 ,9 mg/3L water). The results showed that the highest growth was found in treatment P4 (1.9 mg/3L water) of 4.84 g, the highest absolute length growth was obtained by P4 of 3.00 cm, the highest daily growth rate was obtained in treatment P4 of 3 .96% survival rate 100%, Feed Efficiency 82.83%, and Feed Conversion Ratio 1.21. The results showed that the addition of thyroxine hormone through immersion showed a very significant effect (P<0.05) on absolute weight, absolute length, specific growth rate, feed efficiency, and feed conversion ratio and had no significant effect (p>0.05). to survival. Water quality parameters during the study were still supportive, namely the temperature ranged from 28.0-29.7˚C, water pH ranged from 6.9-8.0, dissolved oxygen (DO) content ranged from 4.0-5.7 ml/ L and ammonia ranged from 0.00015-0.00050 mg/L.